A Prospective Study of Health Conditions Related to Alcohol Consumption Cessation Among 97, 852 Drinkers Aged 45 and Over in Australia. (7th March 2019) - Sarich, Peter; Canfell, Karen; Banks, Emily; Paige, Ellie; Egger, Sam; Joshy, Grace; Korda, Rosemary; Weber, Marianne
Abstract : Background: Evidence suggests that people who develop serious health conditions are likely to cease drinking alcohol (sometimes known as "sick‐quitters"). We quantified the likelihood of quitting drinking in relation to the onset of a variety of health conditions. Methods: Odds ratios (ORs) and 95% confidence intervals (CIs) of ceasing alcohol consumption after diagnosis of 28 health conditions and 4 general indicators of health were derived from logistic regression among 97, 852 drinkers aged ≥ 45 years between baseline (2006 to 2009) and median 5.3 years of follow‐up in the New South Wales 45 and Up Study. Incident health conditions at follow‐up were self‐reported. Results: At follow‐up, 9.6% ( n = 9, 438) of drinkers had ceased drinking. Drinking cessation was significantly associated with 24 of 32 health conditions examined: 15.4% of participants with newly diagnosed diabetes quit drinking (OR for quitting vs. continuing 1.77, 95% CI: 1.60 to 1.96), 16.4% with Parkinson's disease (1.71, 1.35 to 2.17), 17.8% with poor memory (1.68, 1.43 to 1.97), 19.2% with hip fracture (1.64, 1.30 to 2.06), 14.7% with stroke (1.45, 1.27 to 1.66), 12.5% with depression (1.40, 1.26 to 1.55), 15.0% with breast cancer (1.38, 1.18 to 1.61), 12.3% with heart disease (1.34, 1.25 to 1.44), and 13.3% with osteoarthritis (1.22, 1.12 to 1.33). Strong associations with quitting were observed in those with a decline in self‐rated overall health (2.93, 2.53 to 3.40) and quality of life (2.68, 2.24 to 3.21). Some health conditions not significantly associated with quitting were prostate cancer, melanoma, nonmelanoma skin cancer, hay fever, and hearing loss. Findings were generally consistent for men and women, by age group and by smoking status. Conclusions: Diagnosis with a variety of health conditions appears to prompt drinking cessation in older adults. Abstract : Evidence suggests that people who develop serious health conditions are likely to cease drinking alcohol (sometimes known as 'sick–quitters'). We quantified the likelihood of quitting drinking in relation to the onset of a variety of health conditions among 97, 852 Australian drinkers aged ≥45 years. Drinking cessation was significantly associated with 24 of 32 health conditions examined. This research adds to the evidence that 'sick‐quitters' can bias alcohol‐health associations in older age, and must be accounted for in epidemiological studies.